Stress and Anxiety Control as a Result of DHSP Bali's Traditional Meditation and Yoga Practice - Agung Setiabudi; I Gede Eka Agung Agastya Punia; Putu Setiani; Lussy Ayu Puspita; Kadek Satya Manggala (International Journal Labs, 2026)
Stress and anxiety are increasing mental health problems and can have a negative impact on an individual's physical and psychological well-being. Traditional yoga and meditation, including Yoga DHSP Bali, are known as holistic approaches that have the potential to help with stress and anxiety control. Objective: This study aimed to analyze the effect of DHSP Bali Traditional Yoga and Meditation practice on participants' stress and anxiety levels. This study used a pretest-posttest design involving 31 respondents. The intervention in the form of DHSP Bali Yoga practice was carried out for 4 weeks with a frequency of at least 3 times per week. Measurements of levels of depression, anxiety, and stress were carried out using the DASS-42 questionnaire. The results showed an increase in the number of respondents in the normal category and a decrease in the mild to severe category in all dimensions of DASS-42 (depression, anxiety, and stress) after the intervention. A comparison of pretest and posttest scores indicated a decrease in the severity of participants' psychological symptoms. DHSP Bali Traditional Yoga and Meditation Practice is effective in lowering stress and anxiety levels, and has the potential to be a safe and beneficial non-pharmacological complementary therapy in mental health management.